COMPUTER BASED NON TRADITIONAL CONTROL SYSTEM COURSE TEACHING IN INDONESIA ELECTRONICS ENGINEERING POLYTECHNICS EDUCATION - Ekojono, .; Parastiwi, Andriani; Rahmad, Cahya; Rahmanto, Anugrah Nur (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Visual simulation is expected to provide simulation results with a view that allows the students to see and feel like doing the practice of creating a control system. Software control system simulation applications are expected not only easy to use but also interactive to the needs of the computer specifications used are not too sophisticated. In this study the computer based control system course teaching was designed using the combination of an electronics control plant and control system simulation which is called nontraditional control system course teaching. The modelling simulation software application is a solution to see the performance of the controlled system which was developed to implement a control system which is light and easy-to-operate. Spreadsheets can be used to simulate the electronics controlled plant in the development of linear control system which is easy to operate with minimum computer specification that can be used by students. The result of proposed simulation confirms the well-known PID controller effects, and verified by the response of the real DC motor speed electronics control plant developed and can be used as a visual simulation for students of electronics engineering polytechnics students. Modeling simulations to visualize the performance of electronics control circuits are used to overcome the limitations of resources in the laboratory on the administration of polytechnic education in Indonesia. In its implementation in the laboratory, lecturers are encouraged to improve the spreadsheet programming capabilities. The development of this study is that non-traditional electronic control teaching can be implemented through internet of things and cloud computing.